Comparison of CDC and sequence-based molecular typing of syphilis treponemes: tpr and arp loci are variable in multiple samples from the same patient - Mikalová, Lenka; Pospíšilová, Petra; Woznicová, Vladana; Kuklová, Ivana; Zákoucká, Hana; Smajs, David (BMC microbiology, 2013)
BACKGROUND: Molecular typing of syphilis-causing strains provides important epidemiologic data. We tested whether identified molecular subtypes were identical in PCR-positive parallel samples taken from the same patient at a same time. We also tested whether subtype prevalence differs in skin and blood samples. RESULTS: Eighteen syphilis positive patients (showing both positive serology and PCR), with two PCR-typeable parallel samples taken at the same time, were tested with both CDC (Centers for Disease Control and Prevention) and sequence-based typing. Samples taken from 9 of 18 patients were completely typed for TP0136, TP0548, 23S rDNA, arp, and tpr loci. The CDC typing revealed 11 distinct genotypes while the sequence-based typing identified 6 genotypes. When results from molecular typing of TP0136, TP0548, and 23S rDNA were analyzed in samples taken from the same patient, no discrepancies in the identified genotypes were found; however, there were discrepancies in 11 of 18 patients (61.1%) samples relative to the arp and tpr loci. In addition to the above described typing, 127 PCR-positive swabs and whole blood samples were tested for individual genotype frequencies. The repetition number for the arp gene was lower in whole blood (WB) samples compared to swab samples. Similarly, the most common tpr RFLP type "d" was found to have lower occurrence rates in WB samples while type "e" had an increased occurrence in these samples. CONCLUSIONS: Differences in the CDC subtypes identified in parallel samples indicated genetic instability of the arp and tpr loci and suggested limited applicability of the CDC typing system in epidemiological studies. Differences in treponemal genotypes detected in whole blood and swab samples suggested important differences between both compartments and/or differences in adherence of treponeme variants to human cells.
Keywords: Blood; polymorfismus délky restrikčních fragmentů; RNA, Ribosomal, 23S; genetická variace; krev; Genetic Variation; Bacterial Proteins; syfilis; molekulární typizace; Molecular Typing; Humans; Polymorphism, Restriction Fragment Length; Skin; RNA ribozomální 23S; Syphilis; Treponema pallidum; bakteriální proteiny; kůže; lidé